The XXIII International Festival Zodchestvo - Brazhnikova, Inessa (project baikal, 2015)
The results of the XXIII International Festival Zodchestvo are presented. The exposition on the theme of the Festival “New industries. Positive practice of urban development” proposed solutions to such urgent problems as revitalization of Russian monocities, creation of comfortable spaces and integration of architects’ ideas and administrative requirements.
Keywords: Zodchestvo-2015; city renovation projects; new industries; art space; modernization of territories